Odor Classification in Cattle Ranch based on Electronic Nose - Humaira; Hidayat, Rahmat; Wang, Zhi-Hao; Hendrick (International Journal of Data Science, 2021)
Unpleasant smell and pollution are the side effects during the cattle ranch activities. That is the reason why the cattle ranch is placed far from the housing residents. The cattle ranch areas are usually not covered by the internet network, but it is also important to monitoring the pollutant in the cattle ranch. The pollutant gases are also produced during the cattle ranch activities such as hydrogen, oxygen, methane, and carbon dioxide. To classify the odor or unpleasant smell in the air, the electronic Nose (e-Nose) become an effective system to monitor and classify the odor in real time. This research, we proposed an e-Nose system that able to classify the odor in cattle ranch. The Backpropagation method is selected to create the e-Nose model. This e-Nose system is able to transmit data to server without the internet network. The Lora Network has been applied by using point to point method. The web application is also made to display the real time data monitoring and prediction of the odor. Based on our test, the e-Nose accuracy is 99% in real time prediction.